THE MULTI-ROUTE MODEL OF EARLY LEXICAL DEVELOPMENT - Barrett, Martyn D. (Anales de Psicología / Annals of Psychology)
The principal postulates of the multiroute model of early lexical development, which was originally put forward by Barrett (1983a, 1986), are reviewed. It is shown that this model predicts a large variety of different developmental profiles which may be exhibited by individual words during the course of their early acquisition. The empirical evidence which has been obtained in various studies concerning the existence of these predicted developmental profiles is reviewed. It is concluded that this evidence provides strong empirical support for the multi-route model.